Multi-agent-based bus route optimisation for restricting passenger traffic bottlenecks in disaster situations. (2016) - Morimoto, Sayaka; Jinba, Takahiro; Kitagawa, Hiroto; Takadama, Keiki; Majima, Takahiro; Watanabe, Daisuke; Katuhara, Mitujiro
This paper focuses on the passenger traffic bottlenecks occurring in the bus route network in disaster situations and proposes the multi-agent-based bus route network optimisation method to resolve such bottlenecks by generating the networks which can effectively transport many stranded persons who wait around the station as the bottlenecks. For this purpose, the proposed method modifies the bus route networks generated as usual situations to suitably generate the bus lines and redistribute the buses among the lines according to the number of passengers. The intensive simulations have revealed the following implications: the proposed method 1) can optimise the bus route network which is suitable for the bottlenecks; 2) optimises the bus route network which can cope with the hard disaster situations without an additional buses; 3) has the capability of decreasing a risk of the bottlenecks by concentrating on a modification of the lines having the bottleneck stations.